The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1007/s40843-015-0108-4
|View full text |Cite
|
Sign up to set email alerts
|

Basic criterion for the formation of self-organized dislocation patterns in fatigued FCC pure metals

Abstract: tively proposed based on stacking fault energy (SFE).As shown in Fig. 1, PSB ladders or walls are a three-dimensional structure. PSB ladders from t he (12 − 1) plane or PSB walls from the (111) plane occupy about 10% of the PSBs by volume. The walls are 0.03-0.25 μm in thickness with a spacing of about 1.3 μm (see Fig. 2) and they consist of numerous dipoles, especially faulted dipole. The socalled faulted dipole consists of four Shockley partial dislocations and three stacking faults. Th e stair-rods lie at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
1
1
1
Order By: Relevance
“…The damage morphology of SPD Cu is very different from that in FSP Cu observed in this study [3][4][5][6][7][8][9][10]. It is well known that large-scale slip bands, several tens of micrometers in size have been observed on the damaged surfaces of SPD Cu, even at very low stress amplitudes (less than 0.5 UTS) [4,5,7,10,31]. Furthermore, Goto et al [32] indicated that the slip bands formed in ECAP Cu were longer and had an inferior uniformity of distribution density at a lower stress amplitude of 120 MPa, when compared to the slip bands at a high stress amplitude of 240 MPa.…”
contrasting
confidence: 68%
See 1 more Smart Citation
“…The damage morphology of SPD Cu is very different from that in FSP Cu observed in this study [3][4][5][6][7][8][9][10]. It is well known that large-scale slip bands, several tens of micrometers in size have been observed on the damaged surfaces of SPD Cu, even at very low stress amplitudes (less than 0.5 UTS) [4,5,7,10,31]. Furthermore, Goto et al [32] indicated that the slip bands formed in ECAP Cu were longer and had an inferior uniformity of distribution density at a lower stress amplitude of 120 MPa, when compared to the slip bands at a high stress amplitude of 240 MPa.…”
contrasting
confidence: 68%
“…Moreover, many extrusions can be observed protruding from the slip bands, as shown in Fig. 3b, which is similar to that of the single crystal Cu [28,31]. For FSP Cu, no large-scale slip bands could be observed, and no obvious crack initiating sites were found near the fracture edge.…”
supporting
confidence: 60%
“…2 , based on the standing wave effect, the capture of edge segments at the nodes shows that the dislocation loops are bowed out along both sides of the ladders at equal intervals, thus its interval distance is the same as the ladder thickness d w . Meanwhile, the mean interval distance of edge dislocation in the ladders is approximately 8 times as long as the extended dislocation width d ex 33 . Considering Shockley partials in pairs, substituting and into Eq.…”
Section: Discussionmentioning
confidence: 98%